Phase-change perovskite microlaser with tunable polarization vortex - Tian, Jingyi (2023)
Metasurfaces supporting optical bound states in the continuum (BICs) are emerging as simple and compact optical cavities to realize polarization-vortex lasers. The winding of the polarization around the singularity defines topological charges which are generally set by the cavity design and cannot be altered without changing geometrical parameters. Here, a subwavelength-thin phase-change halide perovskite BIC metasurface functioning as a tunable polarization vortex microlaser is demonstrated. Upon the perovskite structural phase transitions, both its refractive index and gain vary substantially, inducing reversible and bistable switching between distinct polarization vortexes underpinned by opposite topological charges. Dynamic tuning and switching of the resulting vector beams may find use in microscopy imaging, particle trapping and manipulation, and optical data storage.